Innovative Teaching Strategies for Kurikulum Merdeka to Improve Education for Indonesian Migrant Children in Jeddah - Atikah Syamsi; Suci Ramdaeni; Misbah Binasdevi (TARBIYA: Journal of Education in Muslim Society, 2024)
AbstractThis study aims to examine the implementation of teacher training on learning innovations within the Kurikulum Merdeka to improve the quality of education for students, particularly Indonesian children living abroad. This community service employs the Asset-Based Community Development (ABCD) approach. The target participants are all 18 elementary school teachers at the Indonesian School in Jeddah. Data collection instruments included both qualitative and quantitative methods, utilizing questionnaires and interviews, before and after the implementation of activities. As a result of this service activity, the teachers at the Indonesian School in Jeddah successfully developed innovative learning media for the Kurikulum Merdeka using digital tools such as Canva and Assembler Edu. Furthermore, the use of digital technology-based learning media significantly motivated students and enhanced their learning experience.AbstrakPenelitian ini bertujuan untuk mengkaji penerapan pelatihan guru tentang inovasi pembelajaran dalam Kurikulum Merdeka untuk meningkatkan kualitas pendidikan bagi siswa, terutama anak-anak Indonesia yang tinggal di luar negeri. Layanan masyarakat ini menggunakan pendekatan Asset-Based Community Development (ABCD). Peserta yang menjadi target adalah semua 18 guru sekolah dasar di Sekolah Indonesia di Jeddah. Instrumen pengumpulan data mencakup metode kualitatif dan kuantitatif, dengan menggunakan kuesioner dan wawancara masing-masing, sebelum dan sesudah pelaksanaan kegiatan. Sebagai hasil dari kegiatan pelayanan ini, para guru di Sekolah Indonesia di Jeddah berhasil mengembangkan media pembelajaran inovatif untuk Kurikulum Merdeka menggunakan alat digital seperti Canva dan Assembler Edu. Selain itu, penggunaan media pembelajaran berbasis teknologi digital secara signifikan memotivasi siswa dan meningkatkan pengalaman belajar mereka.  How to Cite: Syamsi, A., Ramdaeni, S., & Binasdevi Misbah. (2024). Innovative Teaching Strategies for Kurikulum Merdeka to Improve Education for Indonesian Migrant Children in Jeddah. TARBIYA: Journal of Education in Muslim Society, 11(1), 37-46. doi:10.15408/tjems.v11i1.37904